LEGAL PROTECTION AND RESTORATIVE APPROACH IN HANDLING CHILDREN INVOLVED IN TERRORISM CRIMES IN INDONESIA - Sanathana Ishwara, Ade Sathya; Kirana , Sinta Dyah; Safira Erlangga, Vania Lutfi (IBLAM LAW REVIEW, 2024)
This study examines the implementation of restorative justice in handling children involved in terrorism crimes in Indonesia. Restorative justice, which focuses on rehabilitating and reintegrating individuals into society, is a relevant approach to rehabilitating children involved in criminal acts of terrorism. The concept also allows community and victim participation in the settlement process. The study uses normative legal and analytic philosophical approaches. Although restorative justice has the potential to handle terrorism cases involving children, its implementation still faces challenges and requires cooperation from various parties. The research emphasizes that restorative justice should be part of a broader strategy in protecting children from involvement in terrorism, involving effective education, early intervention, and support for families and communities vulnerable to extremist influences. This study also emphasizes that implementing restorative justice in the context of criminal acts of terrorism involving children poses significant challenges and requires cooperation between various parties, including the legal system, educational institutions, families, and communities. The research argues that restorative justice should be an integral part of a broader strategy that involves effective education about the values of peace and tolerance, early intervention to detect and prevent radicalization, and support for families and communities vulnerable to extremist influences.